KEBIJAKAN PEMERINTAH DESA DALAM PENANGGULANGAN ABRASI PANTAI BERDASARKAN PERATURAN PERUNDANG-UNDANGAN DAN PERSPEKTIF ISLAM ( STUDI KASUS PANTAI TANJUNG SENEKIP KABUPATEN BENGKALIS) - Dewi, Irlina; Ika Mulia, Sri; Subekti, Wahyu; Dhea Utari, Yuni; Saifa Abudillah, Mohammad (TERAJU: Jurnal Syariah dan Hukum, 2025)
Teluk Pambang is the outermost, foremost village and is located on Bengkalis Island. From year to year the beach in this village experiences quite severe and worrying erosion. The aim of this research is to determine the village government's policy in efforts to overcome coastal abrasion based on Islamic law and law. The method used in this research is descriptive with a qualitative approach. The results of the research show that the Teluk Pambang Village government has taken policies in accordance with statutory regulations No. 24 of 2007 and Law No. 23 of 2014 which applies, but is not optimal. The policies taken by the Village Government are: (1) Naturally, such as planting (reforestation and rehabilitation) of mangrove forests and api-api trees in areas affected by abrasion. (2) Artificially, through building breakwaters and embankments, (3) Changing the behavior of people around the coast. In the Islamic perspective, coastal erosion is included in environmental damage. There are several solutions in the Koran to overcome environmental damage, namely: (1) Faith and piety, (2) Environmental awareness, and (3) Sustainable management. It is hoped that this research will have a direct impact on environmental management, especially preventing abrasion that occurs on Tanjung Senekip beach, so that in the future this abrasion can be completely resolved.